Interventions to improve the compliance of health care professionals to hand washing: an integrative review - Adriana Cristina de Oliveira; Adriana Oliveira de Paula (Universidade Federal de Goias, 2013)
The objective of this study was to identify the main strategies used to improve the compliance of health care professionals to hand washing. This is an integrative literature review, which search included journals in English, Spanish and Portuguese. Twenty-three articles were included. An electronic tool was developed on Microsoft Office Excel and the main results were submitted to descriptive analysis. Of the total studies, 87.1% had before and after designs and several methods were used to monitor compliance rate (direct observation, supply use and self-reported rates). Multimodal interventions were used in 87.0%, and the most often employed were: education, feedback, alcohol being available and posters. The largest challenge identified was not only improving the compliance rates to hand washing, but, most of all, keeping them high. It was observed there is a need to use multimodal strategies that contribute to behavior change considering the local setting. Descriptors: Hand Disinfection; Health Personnel; Cross Infection; Nursing.